The Intergenerational Conflict in Lisa See’s Shanghai Girls: Second Generation Experiences (NOBEL: Journal of Literature and Language Teaching, 2022)
This study explores the intergeneration conflict and acculturation strategies of the second-generation Chinese American in Lisa See’s Shanghai Girls. The novel depicts Pearl and May’s experiences moving to America due to the Sino-Japanese war in China and facing the cultural conflict of choosing the Chinese or American culture. Therefore, the study uses the sociological approach by employing Hofstede’s cultural dimension and Sam and Berry’s acculturation model to examine the sociocultural experiences of Pearl and May. The result is that the conflict between the first and second generations is based on power distance, masculinity and femininity; individualism and collectivism; and the short and long term. As the result of the conflict, Pearl integrates two cultures on the dimension of power distance and short and long term, while May assimilates more into American culture. Those different strategies also imply the different reception experienced by Pearl and May while socializing within both the Chinese and American cultures.